T Cells in Osteoarthritis: Alterations and Beyond - Li, Yu-sheng; Luo, Wei; Zhu, Shou-an; Lei, Guang-hua (Frontiers in Immunology, 2017)
Although the osteoarthritis (OA) was traditionally regarded as non-inflammatory disease, increasing reports suggest that OA is an inflammatory disease, at least in certain patients. OA patients often exhibit inflammatory infiltrates in the synovial membranes, including macrophages, T cells, mast cells, B cells, plasma cells, natural killer cells, dendritic cells and granulocytes. This review will highlight the current understanding of T cells in the pathogenesis of OA, including Th1 cells, Th2 cells, Th9 cells, Th17 cells, Th22 cells, Treg cells, Tfh cells, cytotoxic T cells, T memory cells, and even unconventional T cells (e.g., γδ T cells and CD1-restricted T cells). These findings highlight the importance of T cells in the development and progression of OA, and open new therapeutic approaches for OA through manipulating the T cell responses.